Reusable and efficient polystyrene immobilized ionic liquid catalyst for batch and flow methylation of hydroquinone - Bhongale, V. Priyanka; Joshi, Sunil S.; Mali, Nilesh A. (Catalysis Letters, 2022)
An environmentally benign process for synthesizing 4-methoxyphenol through methylation of hydroquinone using polystyrene immobilized Bronsted acidic ionic liquid is presented. The catalyst has been characterized by several techniques, such as solid-state NMR, FTIR, and XRD. The morphological properties were analyzed through SEM and TEM analysis. The elemental analysis was performed using EDS and XPS techniques. The catalyst was thermally stable up to 603 K, which was confirmed by TGA. The chemical interaction between ionic liquid and polystyrene was confirmed by measuring the glass transition temperature of pure polystyrene and catalyst. The BET analysis was performed to estimate the catalyst's surface area, pore size, and pore volume. The recyclability of the proposed new catalyst was established up to five recycle runs in the batch mode. In addition, continuous flow experiments were conducted to test the catalytic activity in terms of catalyst life span and showed excellent stability up to 20 h. The rapid separation, long-term stability, and efficient recycling of synthesized polymeric catalysts make an excellent alternative to the commonly used homogeneous catalysts for selective O-methylation of hydroquinone reaction. The newly developed continuous process for synthesizing 4-methoxyphenol with 100% selectivity suggests good opportunities to reduce energy consumption, which designates a cost-effective process. [GRAPHICS] .
Keywords: 4-Methoxyphenol; Hydroquinone; O-methylation; Polystyrene immobilized ionic liquid